Investigating The Microbial Contamination Of Cellular Phones Among Dental Students In Faculty Of Dentistry _ Tishreen University - Amoun, Ammar; Zinab, Asmahan; Kafa, Laura Ali (Latakia University Journal -Medical Sciences Series, 2019)
Infection transmission in dentistry is an inevitable issue that occurs regularly and by different ways as dentists’ mobile phone. The aim of this study was to assess the microbial contamination of cellular phones among students in faculties of dentistry and arts and humanities – Tishreen University and to assess the effectiveness of disinfectant (Cavi Wipes) for decontamination. A questionnaire was completed by participants that consisted of 18 questions about the pattern of using mobile phones and their disinfection. (50) Dental students as a test group and (15) students of faculty of arts and humanities as a control group were enrolled in this study. Sampling was taken from each participant’s phone by a sterile cotton swab moistened by normal saline, two swabs were taken before and after wiping the devices with (Cavi Wipes), then samples were transferred to the laboratory where they were cultured in (Nutrient agar & Blood agar) and allowed to incubate at 37 C for 48 hours. Questionnaire results revealed that 92% of the test group and 60% of the control group believe that mobile phone can serve as a source of pathogens, the study showed that microbial growth was (100%) in all samples from participants mobile phones. A significant difference were found between (CFU/ Colony Forming Units) before and after wiping the devices with (Cavi Wipes) (P-value < 0.05). The present study revealed the potential role of mobile phones as a way of cross contamination between patients and dental staff, in order to minimize the use of mobile phones in the clinical environments and regular disinfecting mobile phones are recommended. يُعد انتقال الإنتان أمراً حتمياً في طب الأسنان، إذ يحدث بكثرة وعبر طرائق متعددة كأجهزة خليوي أطباء الأسنان. تهدف هذه الدراسة لتقييم التلوث الجرثومي على سطوح أجهزة الخليوي لطلاب كليتي طب الأسنان والآداب في جامعة تشرين وتقييم فعالية مناديل (Cavi Wipes) المطهرة في خفض نسبة التلوث المسجلة في هذه الدراسة، حيث تم ملء استبيان للرأي من قبل المشاركين مؤلف من 18 سؤالاً حول طريقة استخدام الأجهزة الخليوية وكيفية تطهيرها. شارك بهذه الدراسة (50) طالباً من كلية طب الأسنان ممثلين لعينة الاختبار، و(15) طالباً من طلاب كلية الآداب ممثلين للعينة الشاهدة. تم أخذ العينات من جهاز كل مشارك عبر ماسحات قطنية مرطبة بمحلول ملحي فيزيولوجي بمعدل مسحتين، وذلك قبل وبعد مسح هذه الأجهزة بمناديل (Cavi Wipes) ثم نقلت العينات إلى المختبر، حيث تم زرعها ضمن أوساط (Nutrient agar)، (Blood agar) وحضنت لمدة 48 ساعة في درجة حرارة 37 درجة مئوية. بينت نتائج استبيان الرأي أن 92 % من عينة الدراسة و60 % من العينة الشاهدة يعتقدون أن الأجهزة الخليوية قد تكون مصدراً محتملاً للإنتانات. أوضحت الدراسة أن النمو الجرثومي بلغ نسبة (100%) في جميع العينات المأخوذة من أجهزة خليوي المشاركين في هذه الدراسة. ووجدت فروقاً ذات دلالة إحصائية مهمة بين معدل المستعمرات النامية على الأوساط وذلك قبل وبعد مسح الأجهزة بمناديل (Cavi Wipes) (P-value < 0.05). تعكس الدراسة الحالية الدور المهم لأجهزة الخليوي كوسيلة لانتقال العدوى بين أفراد الطاقم الطبي السني والمرضى في محاولة لتقليص نسبة استخدامها في البيئات السريرية مع التأكيد على ضرورة التطهير المنتظم لسطوح هذه الأجهزة.